Allocation Fragments of the Distributed Database - Matiasko, Karol (Communications - Scientific letters of the University of Zilina, 2003)
The paper describes the distribution fragments of the database under a mathematical model with criterial function involving the influence of the Transaction and Concurrency proccesing in Database systems. The model could solve variants for replication of the fragments setting constraints in the model. This approach is prepared for revision of actual distribution using real values of the database (cardinality of tables, referential integrity, important requests etc).